Discussing measurement-based care with patients: An analysis of clinician-patient dyads. (17th February 2021) - Brooks Holliday, Stephanie; Hepner, Kimberly A.; Farmer, Carrie M.; Mahmud, Ammarah; Kimerling, Rachel; Smith, Brandy N.; Rosen, Craig
Abstract : Measurement-based care (MBC) refers to the use of three integrated strategies to improve effectiveness of behavioral health care: routine outcomes monitoring using symptom measures; regularly sharing these data with patients; and using these data to inform treatment decisions. This study examined how clinicians discuss MBC data with patients, including identifying what aspects of these discussions contribute to clinician-patient agreement on the value of MBC, and how clinicians use MBC data to inform treatment decisions. Twenty-six clinician-patient dyads participated in semi-structured interviews and provided a treatment session recording in which MBC data were discussed. Qualitative data analyses revealed four subtypes of dyads: clinician and patient both valued MBC; clinician valued MBC, patient passively participated in MBC; clinician valued MBC, patient had mixed perceptions of MBC; clinician and patient reported moderate or low value for MBC. In dyads for whom both the clinician and patient valued MBC, the clinician provided clear and repeated rationale for MBC, discussed data with patients at every administration, and connected observed scores to patient skills or strategies. Emerging best practices for discussing MBC include providing a strong rationale, discussing results frequently, actively engaging patients in discussions, and using graphs to visualize progress.